Sleep-Disordered Breathing and Behavior Problems - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
A community-based cohort of 829 school-aged, 8-11 year-old, children was studied at Case Western Reserve University School of Medicine, Cleveland, OH, to assess the behavioral outcomes of sleep-disordered breathing (SDB), ranging from primary snoring to obstructive sleep apnea (OSA).